Differences in stroke technique of skilled swimmers to exert hand propulsion between the front crawl stroke and the butterfly - Kudo, S.; Miwa, T.; Sakurai, Y. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The arm movement of the front crawl stroke consists of an entry, a down sweep, an in sweep, an upsweep, a release and a recovery while the arm movement of the butterfly consists of an entry, an outsweep, an insweep, an upsweep, a release and a recovery (Maglischo 1993). Both swimming strokes of the front crawl stroke and the butterfly have the insweep and the upsweep phases, which are the main the propulsive phases for both swimming strokes. The front crawl stroke is the fastest stroke among the four competitive strokes, and the butterfly is the second fastest stroke. The butterfly may be considered as the symmetrical stroke of the front crawl stroke in terms of the two stroke phases. Thus, a good front craw stroke swimmer seems to be a good butterfly swimmer. However, the stroke technique to exert hand propulsion in the front crawl stroke is different from the one for the butterfly because the butterfly involves the movement of trunk undulation. The dynamic pressure approach has been developed to quantify hand propulsion exerted by a swimmer, and the hand propulsive technique of skilled sprint-crawl swimmers was re-evaluated (Kudo & Lee 2010; Kudo, Miwa & Sakurai 2013). The dynamic pressure approach also provides information of the hand propulsive drag and lift. By quantifying hand propulsion due to drag and lift forces, hand displacement, velocity and acceleration, we can analyse the detail of hand propulsive technique. The aim of this study was, therefore, to investigate if the hand propulsive technique of the front crawl stroke was different from the one for the butterfly using the dynamic pressure approach.